1976
DOI: 10.1093/jaoac/59.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Food Products for Volatile N-Nitrosamines

Abstract: A variety of food products containing nitrite were analyzed for 14 volatile N-nitrosamines by using a method demonstrated to be sensitive to 10 ppb. A total of 121 food samples were screened for volatile N-nitrosamine content. N-Nitrosopyrrolidine was confirmed in fried bacon at levels up to 139 ppb. N-Dimethylnitrosamine, N-nitrosopyrrolidine, and N-nitrosopiperidine were also confirmed in spice-cure mixtures at levels ranging from 50 to 2000 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…N-Nitrosopyrrolidine (NPYR) (Crosby et al, 1972;Fazio et al, 1973) and to a lesser extent IV-nitrosodimethylamine (NDMA) have been found consistently in fried bacon at the ppb level (Sen et al, 1973;Wasserman et al, 1978), while these and other nitrosamines have been found only sporadically in other cured meat products (Fiddler et al, 1975;Gough et al, 1977;Havery et al, 1976;Panalaks et al, 1974; Wasserman et al, 1972). The presence of nitrosamines in this product may be due primarily to the high cooking temperatures which would favor the reaction of residual nitrite with nitrosatable amine compounds.…”
mentioning
confidence: 98%
“…N-Nitrosopyrrolidine (NPYR) (Crosby et al, 1972;Fazio et al, 1973) and to a lesser extent IV-nitrosodimethylamine (NDMA) have been found consistently in fried bacon at the ppb level (Sen et al, 1973;Wasserman et al, 1978), while these and other nitrosamines have been found only sporadically in other cured meat products (Fiddler et al, 1975;Gough et al, 1977;Havery et al, 1976;Panalaks et al, 1974; Wasserman et al, 1972). The presence of nitrosamines in this product may be due primarily to the high cooking temperatures which would favor the reaction of residual nitrite with nitrosatable amine compounds.…”
mentioning
confidence: 98%
“…The N-nitrosamines detected include N-nitrosodimethylamine, N-nitrosodiethylamine, N-nitrosopyrrolidine, and N-nitrosopiperidine. 89 Acetic acid, 2-methylnitrosamino)-[N-nitrososarcosine] was reported in meat 90 and beer (and malt) 91,92 ; 1-butanamine, N-butyl-N-nitroso-[N-nitrosodibutylamine] in fish 93 ; ethanamine, N-ethyl-N-nitroso-[N-nitrosodiethylamine] in bacon, 94,95 fish, 96 98 cheese, 94,95 powdered milk, 99 beer (and malt), 100,101 gastric juices and nitrite 102,103 ; methanamine, N-methyl-N-nitroso-[N-nitrosodimethylamine] in meat and cured meat, 95,104 –109 bacon, 94,95,110,111 fish, 93 98,112 –121 squid, 114,117 cheese, 94,95,107,108,122 –127 powdered milk, 99,128 –…”
Section: Exposure To Potentially Toxic Chemicals In Common Foods and mentioning
confidence: 99%
“…In addition to their established carcinogenic effect in tobacco, nitrosamines are common contaminants in food throughout the world, found in beer in France in amounts of up to 21.3 microgram/Kg (Klein, Girard, Cabarrou, & Debry, 1980), and in bacon up to 139 microgram/Kg (Havery, Kline, Miletta, Joe, & Fazio, 1976). Food-based nitrosamines are carcinogenic to the oesophagus in animal studies (Lijinsky & Taylor, 1981;Rubio, Liu, Chejfec, & Sveander, 1987;Clark et al, 1994;Seto, Kobori, Shimizu, & Morioka, 1994;Fong, Lau, Huebner, & Magee, 1997).…”
Section: Nitrosaminesmentioning
confidence: 99%